Thesis Overview: Dynamic Gesture Recognition and its Application to Sign Language - Ronchetti, Franco (2017)
The automatic recognition of human gestures is a complex multidisciplinary problem that has not yet been completely solved. Since the advent of digital video capture technologies, there have been attempts to recognize dynamic gestures for different purposes. In the recent years, new technologies such as depth sensors or highresolution cameras were incorporated as well as the high processing capacity of the current devices emerged, allowing the new technologies development capable of detecting different movements and acting in real time. Unlike the recognition of the spoken voice, which has been researched for more than forty years, the topic of this thesis is relatively new in the scientific area and it evolves rapidly as new devices appear as well as new computer vision algorithms.